Sharia Compliance Research by Indonesian Authors Based on Scopus Database: A Bibliometric Analysis - Zuel Fahmi; Samsi; Ahmad Bilal Almagribi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research aims to address the gap in understanding the annual growth and impact of sharia compliance research by Indonesian authors. The focus of this research is to analyze publication trends, main contributors, and collaboration networks using bibliometric methods, utilizing database sources from Scopus and the VOSviewer visualization tool. Based on the analysis, publications on sharia compliance experienced significant annual growth, where Fianto B.A. and Sukmana R. are well-known writers affiliated with Airlangga University. The journals that most frequently contain these publications are the Journal of Islamic Marketing and the Journal of Islamic Accounting and Business Research, with scientific articles being the most common type of document. The subject areas most frequently discussed include business, management, accounting, economics, econometrics, and finance. Collaboration between authors shows strong collaboration, both domestic and international collaboration, especially with authors from Malaysia and Australia. Keywords that appear at the same time (co-occurrence) indicate that sharia banking, corporate governance, and financial performance are the main topics discussed. As for future research, it is recommended that topics related to sharia compliance can be explored further in the context of environmental sustainability, technological innovation, non-financial sectors, and comparative studies, especially in the fields of creative economy and halal tourism.